RANCANG BANGUN SISTEM INFORMASI SATUAN KREDIT PARTISIPASI MAHASISWA FAKULTAS TEKNIK UNIVERSITAS UDAYANA - Agus Satya Dharma, I Gede; Care Khrisne, Duman; Arsa Suyadnya, I Made (Jurnal SPEKTRUM, 2018)
Participation Credit Unit (PCU) is a system of appreciation to Udayana University's students for their participation in student activities in both academic and non academic fields. It is one of the requirements that must be met by every student in order to be allowed to follow graduation. At the Faculty of Engineering of Udayana University, there are some data of students’ PCU that are not stored well, so the data get lost and make the process of inputting the PCU of students become problematic. In this study, the information system being built will be used to manage the PCU data of Faculty of Engineering students of Udayana University. This information system is built by using an HTML programming language, PHP with MySQL DBMS and by using the Bootstrap Framework. The results of the System Usability Scale (SUS) test given to (20) users of the system obtained an average value of 80,88 which means that the it has the values of Excellent Adjective Ratings, B Scale Grade and Acceptable Acceptability Ranges.